I *think* you have done the following:

. . . . .Let A, B, and C be the lengths of the sides of the

. . . . .right triangle, with A = B, and C the hypotenuse.

. . . . .Then:

. . . . .A<sup>2</sup> + B<sup>2</sup> = C<sup>2</sup>

. . . . .But since A = B, we have:

. . . . .A<sup>2</sup> + A<sup>2</sup> = C<sup>2</sup>

. . . . .2 A<sup>2</sup> = C<sup>2</sup>

I'm not sure what you did after that, however...?

Note that the exercise *gives* you the length of C. Try plugging this in. Then solve for A.

Draw the triangle, and note the height and base. Then apply the "area of a triangle" formula.

Eliz.